Analisis Keterampilan Mengajar Mahasiswa Tema „Gegenstände in der Schule“ Pada Matakuliah Micro Teaching - Laili Insyirah Nasywa; Chyntia Pamela Siregar; Cindy Samaria Simorangkir; Novyar Ardhana Pasaribu; Yuni Paulisa Barus; Edo Clinton Damanik; Herlina Jasa Putri Harahap S.Pd.,M.Hum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes students' teaching skills on the theme "Gegenstände in der Schule" in a micro teaching course. Effective teaching is essential in language learning, especially in teaching German. This research used observation and video analysis of students’ micro teaching sessions. Data were evaluated based on teaching skill criteria: lesson planning, implementation, and evaluation. The findings show that students generally understand the material well. However, some areas need improvement, particularly classroom management and student interaction. This study is expected to offer input for curriculum development and teaching strategies in the German language program and help enhance students' teaching competencies.